Adherencia al tratamiento farmaconutricional, actividad física y estado nutricional de adultos con diabetes mellitus tipo 2 del Hospital Regional de Loreto, Iquitos 2022 - Guedez Garces, Eskarleth Jherilyn (2023)
The research determined the relationship between adherence to pharmaco-nutritional treatment and physical activity, with the nutritional status of adults with type 2 diabetes mellitus (DM2) who attend the outpatient clinic for noncommunicable diseases of the Regional Hospital of Loreto, through a descriptive study of non-experimental type with correlational design. Data on nutritional status were collected using anthropometric and biochemical techniques, through a pharma-nutritional adherence survey and IPAQ questionnaire for physical activity, with a sample of 238 patients with DM2; applying descriptive statistics and correlational analysis using Spearman's Rho, it was shown that those evaluated present a normal nutritional status of 36.1% and overweight of 40.8%, likewise, a high adherence to pharmaconutritional treatment was observed with 84.8 % and 67.6% perform physical activity, it was observed that the highest percentage (67.6%) and 5.5% low physical activity. There is no significant relationship (p>0.05) between nutritional status and adherence, a weak significant relationship (p<0.05) was evidenced between nutritional status and physical activity.